Physiology and pathophysiology of IGFBP-1 and IGFBP-2 – Consensus and dissent on metabolic control and malignant potential. Issue 5 (October 2015) - Hoeflich, Andreas; Russo, Vincenzo C.
Abstract : IGFBP-1 and IGFBP-2 are suppressed by growth hormone and therefore represent less prominent members of the IGFBP family when compared to IGFBP-3 that carries most of the IGFs during circulation under normal conditions in humans in vivo. As soon as the GH signal is decreased expression of IGF-I and IGFBP-3 is reduced. Under conditions of lowered suppression by GH the time seems come for IGFBP-1 and IGFBP-2. Both IGFBPs are potent effectors of growth and metabolism. Secretion of IGFBP-1 and IGFBP-2 is further suppressed by insulin and diminished with increasing obesity. Both IGFBP family members share the RGD sequence motif that mediates binding to integrins and is linked to PTEN/PI3K signalling. In mice, IGFBP-2 prevents age- and diet-dependent glucose insensitivity and blocks differentiation of preadipocytes. The latter function is modulated by two distinct heparin-binding domains of IGFBP-2 which are lacking in IGFBP-1. IGFBP-2 is further regulated by leptin and has been demonstrated to affect insulin sensitivity and glucose tolerance, further supporting a particular role of IGFBP-2 in glucose and fat metabolism. Since IGFBP-2 is controlled by sex steroids as well, we devised a scheme to compare IGFBP effects in breast, ovarian and prostate cancer. While a positive association does not seem to exist with IGFBP-1 and risk of cancers within these reproductive tissues, a relationship between IGFBP-2 and breast cancer, ovarian cancer and prostate cancer does indeed appear to be present. To date, the specific roles of IGFBP-2 in estrogen signalling are unclear, though there is accumulating evidence for an effect of IGFBP-2 on PI3K signalling via PTEN, particularly in breast cancer.